Pertanggungjawaban atas Perdagangan Minuman Beralkohol terhadap Anak dibawah Umur Melalui Layanan Go-Shop di Kota Denpasar - I Made Krisna Bagus Wisena; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
This increasingly popular digital world is marked by the emergence of the internet and various devices or gadgets, the Go-Shop service feature on Go-Jek makes it easy for users to get goods including alcoholic beverages so there needs to be accountability for the affordability of alcoholic beverages purchases by minors. The purpose of this study is to discuss the factors that cause the sale of affordable alcoholic beverages to minors on Go-Shop services and to describe the form of accountability for alcoholic beverages traded to minors through Go-Shop services at Go-Jek in Denpasar City. The research method in this article uses empirical research methods, using a sociological approach, and a statutory approach. Sources of legal materials consist of: primary and secondary sources of legal materials. The data sources used were traced by document study techniques centered on legislation and various literature relevant to the object of research as well as interview techniques conducted on informants and respondents. As for the results of this study, it can be concluded that the internal factors of underage children consume alcohol out of curiosity, while the external factors are due to social influences, especially association. Regarding the accountability for the affordable purchase of alcoholic beverages by minors, it can be addressed to partners or even parents or guardians of minors, as well as PT Go-Jek.